Molecular Identification of Taenia hydatigena from Goats in Khishig-Undur, Mongolia - Janchiv, Temuujin; Chultemsuren, Yeruult; Zagd, Amarbayasgalan; Tangad, Mungunzaya; Tileubai, Akhiit; Baldandorj, Bolorchimeg; Badrakh, Burmaa; Uudus, Bayarsaikhan; Wandra, Toni; Budke, Christine M; Janchiv, Khulan; Baldorj, Ochirkhuyag; et al. (Jurnal Veteriner, 2023)
Cysticercosis caused by the larval form of the Taenia hydatigena tapeworm poses a global challenge to the livestock industry. A total of 56 goats slaughtered in Khishig-Undur, Mongolia were evaluated for the presence of cystic lesions. Collected cysts were assessed using the mitochondrial 12S rRNA gene. In total, 46.4% (26/56) of evaluated goats were positive for T. hydatigena infection, with most cysts attached to the omentum, mesentery, liver, or spleen. Partial 12S rRNA gene sequences were obtained from all evaluated cysts and aligned with known sequences for T. hydatigena. Infection prevalence was higher in goats three years of age and older (50.0%; 17/34) compared to goats less than three years of age (40.0%; 9/22) (p=0.035). Infection with T. hydatigena appears to be highly prevalent in goats in Khishig-Undur. Additional studies are needed to evaluate local parasite transmission dynamics and the impact of this parasite on local livestock production.